Prospects of transition to European standards – features of Eurocode 8 - Viktosenko, I.A.; Dovbnich, M.M.; Mazanec, M. (Geofizicheskiy Zhurnal, 2025)
This paper analyzes the features of Eurocode-8, the European standard for earthquake-resistant construction, regarding seismic microzonation and seismic hazard assessment. The standard is compared to the methodology of similar studies in Ukraine. There is a significant difference in approaches to considering local near-surface geological conditions of survey sites. The study shows the critical role of shear-wave velocity in the uppermost subsurface as a primary indicator of a site’s seismic response. It explores innovative approaches to obtaining velocity characteristics based on multichannel analysis of surface waves and modeling regional near-surface velocity based on Shuttle Radar Topography Mission data. The key issue of implementing Eurocode-8 requirements in Ukrainian conditions is discussed, with a particular focus on making seismic hazard map based on peak ground acceleration.